The Use of Artificial Intelligence in Enhancing Customer Relationship Management (CRM): A Systematic Literature Review - Nugraha, Zahra Sabila; Muhammad, Maulana Asykari; Waspodo, Bayu (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
Customer Relationship Management (CRM) has become a key business strategy for retaining customers. As data continues to grow in variety and volume, more advanced solutions are needed. The integration of Artificial Intelligence (AI), CRM, and Big Data offers promising support in addressing modern business challenges in the era of digitalization. This study explores the application of Artificial Intelligence in Customer Relationship Management (AI-CRM) through a literature review. We adopted the Kitchenham and Charters method for conducting the review and initially identified 356 studies. Data were collected from 33 studies published in the Scopus, ScienceDirect, and IEEE databases between 2020 and 2025. The results show that supervised learning remains the most widely used AI technique, while deep learning has grown significantly in recent years, indicating a shift toward more sophisticated CRM solutions. Most applications were found in Analytical CRM, particularly for churn prediction, customer segmentation, and personalization. However, challenges related to data quality, bias, privacy, and transparency remain prevalent. Additionally, areas such as B2B and Strategic CRM remain underexplored. This review emphasizes the need for organizational readiness before adopting AI-CRM and highlights AI’s transformative potential to enhance CRM strategies and gain a competitive advantage. The findings deliver useful insights into the application of AI in data-driven CRM.